The Development Of Information Technology In Human Resource Management In Industry Sector In Malaysia - Kiat, Soon Seng (2002)
The development of Information Technology and e-Business are no less dramatic for Human Resource Management in the industry sector in Malaysia. The survey has shown that the conventional Human Resources Management have been heavily weighted in administration process. The evolution of Information technology has forced Human resources to focus on strategies to support the company business. The development of Human Resource Information Technology system or eHR has improved the overall HR effectiveness and efficiency . eHR is an electronic communication network designed to integrate business, process management, administrative objective and streamlining Human resources service delivery.